Ethycal and Legal Problems Restriction on Dental Services During Health Pandemic - Sri Rahayu; Endang Wahyati Yustina; Hari Pudjo Nugroho (Universitas Katolik Soegijapranata Semarang, 2021)
Abstract։ The COVID-19 pandemic has spread all over the world. Based on Presidential Decree No. 11 of 2020, Indonesia was declared in a COVID-19 pandemic situation. The ever-widening spread of Covid 19 prompted PB PDGI to issue Circular Letter Number: 2776/PB PDGI/III-3/2020 concerning Guidelines for Dental Services During the Covid 19 Pandemic, which regulates the restriction on dental services. Research on the implementation of dental services during the pandemic was carried out by a socio-legal research approach, collecting primary data with questionnaires for patients and dentists at the public health centre, clinics, hospitals, and dental practitioners, who practised during the pandemic. Data were analyzed by the chi-square method and qualitative analysis method. Interviews with the management of health facilities and professional organizations to determine the sociological conditions that affect them. Guidelines for the Prevention and Control of Covid 19 published by the Ministry of Health in July 2020, stipulate that basic health care efforts are given based on priorities by considering the benefits, risks and efforts to control Covid 19, by reducing face-to-face contact and developing telemedicine. In all types of health facilities, dentists still provide emergency services, there are differences in elective dental procedures, which bring up ethical and legal problems. Health service restrictions as regulated in the Covid 19 Prevention and Control Guidelines, reduce the patient's right to obtain health services according to medical standards, not by the 1945 Constitution Article 28 H paragraph (1) and Law number 6 of 2018 concerning Health Quarantine Article 8 The circular letter of PB PDGI regarding Guidelines for Dental Services during the Covid Pandemic has no legal force, the authority to determine medical service guidelines for the minister of health, and the circular does not include the hierarchy of laws regulated in Article 7 and 8 of Law No. 12 of 2011. Dental services during the pandemic were influenced by normative, sociological and technical factors. Cooperation between state institutions, local governments and professional organizations is needed so that the arrangements can solve the problems. Abstrak: Pandemi Covid 19 telah menyebar ke berbagai penjuru dunia. Berdasarkan Keputusan Presiden Nomor 11 tahun 2020 Indonesia dinyatakan dalam situasi pandemi Covid 19. Penyebaran Covid 19 yang terus meluas mendorong PB PDGI mengeluarkan Surat Edaran Nomor: 2776/PB PDGI/III-3/2020 tentang Pedoman Pelayanan Kedokteran Gigi Pada Masa Pandemi Covid 19, yang mengatur adanya pembatasan pelayanan kedokteran gigi . Penelitian pelaksanaan pelayanan kedokteran gigi di masa pandemi dilakukan dengan metode pendekatan socio-legal research, pengumpulan data primer dengan kuesioner terhadap pasien dan dokter gigi di puskesmas, klinik, rumah sakit, dan praktek perorangan, yang berpraktek selama masa pandemi. Data dianalisis dengan metode chi square dan metode analisa kualitatif. Wawancara dengan manajemen fasilitas kesehatan dan organisasi profesi untuk mengetahui kondisi sosiologi yang mempengaruhi. Pedoman Pencegahan dan Pengendalian Covid 19 diterbitkan Kementerian Kesehatan pada Juli 2020, mengatur bahwa upaya pelayanan kesehatan dasar, diberikan berdasarkan prioritas dengan mempertimbangkan, manfaat, risiko dan upaya pengendalian Covid 19, dengan langkah mengurangi tatap muka dan mengembangkan telemedicine. Pada semua jenis fasilitas kesehatan, dokter gigi tetap memberikan pelayanan kegawatdaruratan, terdapat perbedaan dalam pelayanan tindakan elektif, yang menimbulkan problema etika dan hukum. Pembatasan pelayanan sebagaimana di atur dalam Pedoman Pencegahan dan Pengedalian Covid 19, mengurangi hak pasien untuk mendapatkan pelayanan kesehatan sesuai standar kedokteran, tidak sesuai dengan Undang Undang Dasar 1945 pasal 28 H ayat (1) dan Undang Undang nomor 6 tahun 2018 tentang Kekarantinaan Kesehatan Pasal 8. Surat edaran PB PDGI tentang Pedoman Pelayanan Gigi pada Masa Pandemi Covid tidak mempunyai kekuatan hukum, kewenangan penetapan pedoman pelayanan kedokteran pada menteri kesehatan, dan surat edaran tidak termasuk hirarki perundang-undangan yang diatur dalam Pasal 7 dan Pasal 8 UU no 12 tahun 2011 tentang Pebentukan Peraturan Perundang-undangan. Pelayanan kedokteran gigi di masa pandemi dipengaruhi faktor normatif, sosiologis dan teknis. Perlu kerjasama antar lembaga negara, pemerintah daerah dan organisasi profesi agar pengaturan yang disusun menjawab permasalahan.